Case Report of Long-Term Results of Biaxial and Volz Total Wrist Arthroplasty - Ekroth, Scott R.; Werner, Frederick W.; Palmer, Andrew K. (Journal of Wrist Surgery, 2012)
The purpose of this case report was to look at the long-term (average 17.8 years) results of total wrist arthroplasty. Of the 12 wrists (9 patients) available for evaluation, 7 wrists still had the arthroplasty in place whereas 5 wrists had been revised to an arthrodesis. The average age at time of arthroplasty for those requiring an arthrodesis was 17 years less than those not requiring an arthrodesis. This suggests that there is a higher incidence of loosening when total wrist arthroplasty is performed in younger patients, perhaps due to these younger patients having higher demands or having more severe rheumatoid arthritis. In this younger population, the implant metacarpal stem cut out in three wrists and ulnar drift occurred in two wrists. All patients said that if given the chance, they would have a total wrist arthroplasty again, despite their long-term results being poor and many of them being revised to a wrist arthrodesis.
Keywords: wrist arthroplasty; wrist; implants